Staying Relevant: Radio’s Shift Toward Gen Z’s Listening Habits - Jati, Rocky Prasetyo (JURNAL KOMUNIKASI INDONESIA, 2026)
The digital transformation of media has reshaped audio consumption and challenged traditional radio to stay relevant, particularly among Generation Z, the digital-native cohort. This article examines how community and hyperlocal radio stations are adapting to shifting media dynamics by combining conventional broadcasting with digital innovations. The study employs qualitative methods. As Gen Z prefers flexible, personalized, and on-demand content, radio stations are repositioning broadcasters as multi-platform content creators and online community managers. Adaptation strategies include integrating radio with visually oriented social media platforms, offering curated playlists, and adopting participatory models such as digital tipping (saweran). Radio stations are also starting to utilize data analytics to enhance content personalization and audience relevance. The article argues that radio’s sustainability in the digital era depends not only on technological adaptation but also on its ability to maintain cultural resonance, emotional connection, and active engagement. By applying theoretical frameworks of Uses and Gratifications, Cultural Participation, and Cultural Memory, this study shows how radio can evolve into a hybrid media platform that blends spontaneity, personalization, and community-based interaction. Ultimately, this positions radio as both an innovative and culturally embedded medium capable of sustaining its relevance in the evolving media landscape of the digital generation. Keywords: digital media consumption, digital native, generation Z, radio broadcasts, media transformation